Tietze’s Extension Theorem for Intuitionistic Fuzzy ζ-Basically Disconnected Spaces in Katetov-Tong’s Sense - S. Sharmila; I. Arockiarani (International Journal of Mathematics And its Applications, 2015)
In this paper we initiate the concept of ζ-basically disconnectedness in intuitionistic fuzzy topological spaces. We also apply these notions of ζ-basically disconnectedness to analyse and prove Tietze extension theorem.